Counter Cyber Terrorism Governance In Indonesia - Arlan Siddha; Renaldo Benarrivo (UIN Sunan Gunung Djati, 2023)
Information and communication technology has a significant impact on various aspects. Its developments affect daily life, and also give a new color to the political-security dynamics, especially in Indonesia. This depends on the purpose of using information and communication technology, which if not regulated, will become a double-edged sword. The typology of threats is also increasingly varied and transforming, including in the context of security threats in the form of terrorism which involves many dimensions ranging from religion-based terrorism to cyber-based terrorism. The state's response to cyber terrorism as a new security threat phenomenon is examined in this paper in a balanced way using an inward-looking and outward-looking perspective. By using qualitative research methods and descriptive research types, the existing data related to what has been done by Indonesia are interpreted into the form of a governance conception in the context of countering cyber terrorism. Indonesia has identified domestic conditions to be able to optimize its resources. At the same time, Indonesia is also trying to improve its capabilities by conducting international cooperation. So that the governance of countering cyber terrorism in Indonesia still leaves several problems that need to be resolved, such as institutional barriers including organizational culture which is the key to coordination between institutions related to countering cyber terrorism in Indonesia.